Correction to: Alternatives to the EM algorithm for ML estimation of location, scatter matrix, and degree of freedom of the Student t distribution - Hasannasab, Marzieh; Hertrich, Johannes; Laus, Friederike; Steidl, Gabriele (Numerical algorithms, 2021)
A Correction to this paper has been published: https://doi.org/10.1007/s11075-021-01156-z